Male and female sterility in Zambia - Pantazis, Athena (Demogr Res, 2014)
BACKGROUND: Population measures of sterility are traditionally constructed for women, despite fertility and sterility being conditions of the couple. Estimates of male sterility provide insight into population-level sterility, and complement estimates based solely on women. OBJECTIVE: This study seeks to estimate male sterility for the Gwembe Tonga of Zambia using male birth histories collected by the Gwembe Tonga Research Project from 1957 to 1995, while providing context by estimating female sterility for the Gwembe Tonga, as well as female sterility in all of Zambia, from Zambian DHS data (1992, 1997, 2001–02, and 2007). METHODS: Sterility is measured using the Larson-Menken subsequently infertile indicator. Estimates are produced using discrete time event history analysis. RESULTS: The odds of sterility were higher for women than men, though women’s odds of sterility were only 1.5 times that of men’s in the middle reproductive years. The odds of sterility increased steadily with age for both men and women, and across all datasets. However, women’s sterility increased much more sharply with age than men’s did, and women’s odds of sterility were higher than men’s at all reproductive ages.